Habit nail tic disorder: onychotillomania involving thumbs and toes responding to fluoxetine - Bose, Akash; Maji, Taniya; Datta, Subhendu; Mallik, Nitu; Bandyopadhyay, Gautam Kumar (International Journal of Research in Medical Sciences, 2024)
Habit nail tic disorder is a type of nail dystrophy caused by repetitive trauma to the nail matrix. It is a body-focused repetitive behavior that is commonly reported among adults and may or may not be associated with obsessive-compulsive behavior. In this report, we present a case of a 12-year-old adolescent girl who had a central furrow with longitudinal ridges running parallel from the proximal to the distal end of both her thumbnails and toenails, giving them a "washboard" appearance and diagnosed as habit nail tic disorder, and treatment involved fluoxetine 20 mg and the application of permeable adhesive tape to protect the nails from external trauma. There was a positive response observed two months after the beginning of the treatment and the nail matrix resolved spontaneously.